OPTIMALISASI KESEIMBANGAN LINTASAN PRODUKSI DENGAN METODE LARGEST CANDIDATE RULE DI PT. PAP - edy edy; Mifthahul Ahyan (Universitas Harapan Medan, 2020)
Research on the optimization of the balance of the production line was conducted at PT. PAP, which is a manufacturing company in the tire retreading industry. The not yet optimal production line has the potential to cause bottlenecks on the production line. The existence of workload imbalance can be seen from the significant variation in idle time from each work station. For this reason, this study was conducted with the aim of optimizing the line balancing which refers to indicators such as: balance delay, line efficiency and total idle time. The method used in this study is the Largest Candidate Rule (LCR) method which is part of the heuristic method. The use of heuristic methods is basically designed to get better results based on certain limitations. From the research results obtained: Balance Delay (D) = 25.05%, Line Efficiency (LE) = 74.95%, and the total idle time is 1.515 seconds. When compared with the initial state before optimization, the results are a decrease in Balance Delay (D) of 28.44%, an increase in Line Efficiency (LE) of 28.44%, and a reduction in total idle time of 3,699 seconds.